The cyanobacterial toxin, microcystin-LR, can induce apoptosis in a variety of cell types - McDermott, CM; Nho, CW; Howard, W; Holton, B (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
Cyanobacterial toxins; especially the microcystins (MCYST), are found in eutrophied waters throughout the world. These toxins cause hepatocyte damage by inhibiting protein phosphatases and 2A, resulting in hyperphosphorylation of cytoskeletal proteins. Acute intoxication of animals and humans has been reported following MCYST exposure. Okadaic acid, a marine biotoxin, has a similar mechanism of action to MCYST and has been shown to cause apoptosis, a form of programmed cell death, in a variety of cell types. In this study, primary rat hepatocytes (in suspension and monolayer culture), human fibroblasts, human endothelial cells, human epithelial cells, and rat promyelocytes were observed following treatment with MCYST for morphological and biochemical changes typical of apoptosis. Hepatocytes underwent cell membrane blebbing, cell shrinkage, organelle redistribution, and chromatin condensation as early as 30 min following MCYST application (0.8 mu M). Other cell types treated with MCYST (100 mu M) also showed these morphological changes, but required a longer period of treatment. DNA fragmentation and "ladder" formation occurred in most cell types exposed to MCYST. These observations demonstrate that MCYST causes apoptosis in a variety of mammalian cells. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: PROTEIN PHOSPHATASES; DNA FRAGMENTATION; OKADAIC ACID; POLY(ADP-RIBOSE) POLYMERASE; MAMMALIAN-CELLS; PEPTIDE TOXIN; HEPATOCYTES; AERUGINOSA; INHIBITION; DEATH